Effect of Strontium Ranelate on Condylar Growth during Mandibular Advancement in Rats - Hasan Camcı; Cenk Doruk; Serpil Ünver Saraydın (Galenos Yayinevi, 2020)
Objective:Strontium ranelate (SR), unlike other anti-osteoporotic agents, might not only prevent bone resorption but also might induce bone formation. The aim of this experimental study was to evaluate the effects of systemic SR on condylar growth during mandibular advancement (MA) in growing rats.Methods:Fifty-six, 8-week-old Wistar male rats weighting 160-190 g were randomly divided into four groups; one control (n=14) and three experimental (n=14). Group 1: Control group, Group 2: SR (900mg/kg daily dose), Group 3: MA, Group 4: SR +MA. The amount and direction of mandibular growth were assessed by linear measurements on the computed tomography (CT) images taken on days 1, 15, and 30. For immunohistochemical evaluation, half of the subjects in the groups were sacrificed on the 15th day (early phase) and the rest of them on the 30th day (late phase). New cartilage and bone formation areas on the condyle were analyzed by using Sox9 and Osteopontin antibodies.Results:Early and late CT images measurements showed no significant difference between the groups (p<0.05). However, there were significant differences between the control and experimental groups in the immunohistochemical assessment. Severe immunolocalization of SOX9 and Osteopontin was observed in Group 4, while the immunolocalization scores were moderate in Group 2 and Group 3. In addition, early histological findings were similar to late results in all groups.Conclusion:In mandibular advancement therapy, Strontium ranelate could be therapeutically effective in avoiding relapse and reducing the duration of retention.